Perjuangan Tokoh Perempuan dalam Novel Melangkah Karya J.S. Khairen - Parmila, Wisa; Deliani, Susy; Muliatik, Sri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this study was to find out: 1) Describe the social life of female characters in the novel Melangkah by J.S. Khairen. 2) To describe the forms of struggle of female characters in the novel Melangkah by J.S. Khairen. 3) To describe the factors that influence the struggle of female characters in the novel Melangkah by J.S. Khairen. The research method used in this study is descriptive qualitative method. This research is included in post-modern feminism. As for this study, researchers analyzed the form of struggle of female characters which is divided into 3, namely: willing to sacrifice, never give up, and resistance. Meanwhile, the struggle factors are divided into 4 parts: family, friends, love for the country, and culture. The female characters in the analyzed novel are Aura, Siti, and Ocha. From the results of this study, it can be found that the social life of female characters in the novel Melangkah by J.S. Khairen is 15 in the character Aura, 4 in the character Siti, and 2 in the character Ocha. The form of struggle for female characters in the novel Melangkah by J.S. Khairen is 15 for Aura, 2 for Siti, and 3 for Ocha. There are 20 findings on the struggle factors of female characters in the novel Melangkah by J.S. Khairen, namely: family 1, friends 7, love for the country 10, and culture 2.